Inverted pendulum virtual control laboratory - António Paulo Moreira (2006)
This paper describes a tool for interactive learning that can be used to improve control systems design. The developed system is ready to use and allows testing different control methods. It can be used by students for problem solving and individual learning. The virtual control laboratory was implemented as a teaching aid during lectures on control systems. As there is no need to do any special programming or debugging, the students can focus on the control items. Classical control methods such as PID and State-Space approaches are available and gains can be tuned. A friendly appearance based on openGL 3D shows a simulation of the real word: A cart with an inverted pendulum is bumped with a force. The dynamic equations of motion for the control system are linearized assuming that the pendulum does not move more than a few degrees away from the vertical allowing to apply linear control methods. Although, the simulated system is realistic and based on a Dynamics Engine.